THE WHOLE WORLD AROUND ONE BALL - Amangul Saparbayevna Yusupbayeva (Modern American Journals, 2025)
The world's most viewed sporting event is the FIFA World Cup. The historical evolution of football as a sport, its playing methods, and the possibilities and circumstances established for Uzbek football players are all covered in this article.
Keywords: Tiny fields, leather balls, teamwork, football, game tactics, Eastern peoples, physical development, sports outcomes, technical approaches, and moral and volitional attributes.